Effect of Merger and Acquisition of Deposit Money Banks on Nigeria’s Economic Growth: A Pre and Post Analysis - B.L.O., Kazeem; A. O. , Ademola; A.D., Ogunlokun (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2022)
The study examined the effect of Mergers and Acquisitions (M&As) of Deposit Money Banks (DMBs) on Nigeria’s economic growth. Pre-M&As period lasted from 1990–2004, while the Post-M&As spanned from 2005–2019. Data was collected from the Central Bank of Nigeria (CBN) Statistical Bulletin and tested with Ordinary Least Square Regression Analysis. The results indicated that in the Pre-M&As era, bank’s capital base, credit granted to the private sector and bank spread positively, enhanced economic growth howbeit and bank’s gross credit adversely affected economic growth. Findings also revealed that Post-M&As era contradicted the Pre-M&As effect on DMBs, with all the bank indicators showing negative connection with economic growth, except credit granted to the private sector. These findings led to the conclusion that M&As had little impact on the country’s economic growth during the period under consideration. As a result, the study recommendedthat the CBN issue a special directive to the DMBs to extend more credit to the private sector as a means of accelerating economic growth.